Mental Imagery and Attentional Style in Senior Mini-Football Players - Adela Badau (BRAIN. Broad Research in Artificial Intelligence and Neuroscience, 2024)
The purpose of this study was to determine the level of mental imagery ability and attentional style in senior mini-football players and to identify mental behavioral patterns. The study included a number of 38 senior mini-football players, with an average age of 27.36 years, with a playing experience in the super league of 9.38 years. In the study, two standardized questionnaires were applied, one aimed at identifying the level of mental imagery called the Questionnaire for the Assessment of Mental Imaginative Abilities in Athletes (QMIA) with 16 items and one for identifying the attentional style with the aim of determining internal or external dimensions, called the Questionnaire for Assessment of the Attentional Style in Athletes (QASA) with 6 items, structured in two subscales A and B. The calculated reliability of the questionnaire: QMIA had the Cronbach's Î± value of 0.811 and QASA registered a good reliability evidenced by Cronbach's Î± of 0.765 for the entire questionnaire; the internal attentional subscale of 0.728, and for the external attentional subscale of 0.726. After analyzing the results, a good level of mental imagery was found that can be perfected, identifying four behavioral patterns. The attentional style highlighted an internal dimension, which highlighted 3 behavioral patterns. At the level of senior mini-football players, in addition to physical, technical and tactical training, psychological training plays an essential role. Cognitive abilities regarding mental imagery and attention are psychological foundations whose development contributes to obtaining significant sports performances in the mini-football game.
-
Keywords: attentional style; mini-football players; behavioral patent; mental imagery